Status Kewarganegaraan Ganda Dilihat dari Perspektif Undang-Undang Nomor 12 Tahun 2006 tentang Kewarganegaraan Republik Indonesia - Glery Lazuardi (CV. Social Politic Genius (SIGn), 2020)
This study aims to analyze the status of dual citizenship in terms of Law Number 12 of 2006 on Citizenship of the Republic of Indonesia. This research uses normative legal research methods. Normative legal research is research conducted by conducting a study of statutory regulations, namely Law Number 12 of 2006 on Citizenship of the Republic of Indonesia, whether it is relevant to be applied to a legal problem. The legal problem in this study is the citizenship status of Gloria Natapradja. In 2016, Gloria Natapradja was dismissed as an official of the Heirloom Flag raiser after having French citizenship, who followed the citizenship of her biological father. After conducting research, it is known, the state has an obligation to protect the rights of citizens. The state should pay attention and protect citizens regarding the status of citizens. The problems experienced by Gloria Natapradja, because citizenship status can be seen as not yet the maximum role of the government to protect citizens. The issue of citizenship in Gloria Natapradja requires the government to review the regulation of citizenship status as regulated in Law Number 12 of 2006 on Citizenship of the Republic of Indonesia.